2015
DOI: 10.1007/s00246-015-1205-6
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Reference Values in Pediatric Cardiopulmonary Exercise Testing

Abstract: Cardiopulmonary exercise testing (CPET) is used for the diagnosis and prognosis of cardiovascular and pulmonary conditions in children and adolescents. Several authors have published reference values for pediatric CPET, but evaluation of their validity is lacking. The aim of this study was to review pediatric CPET references values published between 1980 and 2014. We specifically assessed the adequacy of the normalization methods used to adjust for body size. Articles that proposed references values were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…As mentioned here, we found linear increase of minute ventilation during work to peak of 80.03±27.8 L/ min, as a result of linear increase of tidal volume and breathing frequency. As previous fi ndings report that boys reached signifi cantly higher peak VE compared with girls, this is consistent with our fi ndings (27)(28)(29)(30). In correlation with our fi nding at rest, boys had signifi cantly higher lung volumes (29).…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…As mentioned here, we found linear increase of minute ventilation during work to peak of 80.03±27.8 L/ min, as a result of linear increase of tidal volume and breathing frequency. As previous fi ndings report that boys reached signifi cantly higher peak VE compared with girls, this is consistent with our fi ndings (27)(28)(29)(30). In correlation with our fi nding at rest, boys had signifi cantly higher lung volumes (29).…”
Section: Figuresupporting
confidence: 93%
“…Both girls and boys showed gradual reduction of dead space ventilation during incremental work. Previous studies showed no sex diff erences in breathing frequency increase, VE /VCO2, and end-tidal PCO2 (3,9,(27)(28)(29)(30). The VE/VCO2 slope may represent gas exchange effi ciency during exercise or equivalent of the number of liters of air that must be breathed out to eliminate 1 liter of CO2.…”
Section: Figurementioning
confidence: 97%
“…These reference values provide a quantitative description of a healthy response to exercise and add to other pediatric exercise testing reference values [17,33]. Clinicians cannot determine an unhealthy response if they do not know what a healthy response is.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Despite the clinical significance of SBP values for children and its relatively inexpensive way to record them, there is a lack of prevalent normative data. In 2015, a systematic review of all studies that offered reference values of pediatric CPET between 1980 and 2014 was done [17]. Not one of these studies included reference values for SBP.…”
Section: Introductionmentioning
confidence: 99%
“…18 Various shortcomings of these studies hinder implementation of the protocols in clinical practice.…”
Section: Normative Values For the Fitkids Treadmill Testmentioning
confidence: 99%